2019
DOI: 10.1029/2018jc014918
|View full text |Cite
|
Sign up to set email alerts
|

Decadal Variability of the Barrier Layer and Forcing Mechanism in the Bay of Bengal

Abstract: Using Simple Ocean Data Assimilation data set for 1951–2010, we analyze the decadal variability of barrier layer thickness (BLT) and its forcing mechanisms in the Bay of Bengal (BoB). The decadal variability of BLT shows a close connection with the Pacific Decadal Oscillation (PDO). The PDO‐induced spatial distribution of BLT is similar to its first Empirical Orthogonal Function mode, showing a meridional dipolar pattern. PDO can exert an influence on the decadal variations in the Walker circulation to indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In the western Pacific warm pool, sea surface freshwater forcing, including the heavy rain under ITCZ and high salinity water subduction from subtropics, are the dominant processes for the BL formation (Anderson et al., 1996; Bosc et al., 2009). Positive BLT anomalies along the eastern and northern coast of the Bay of Bengal during a positive Pacific Decadal Oscillation (PDO) are associated with deepening ILD, referring to enhancing shoreward Ekman transport (Pang et al., 2019). As discussed in Section 4, the BL formations in different seasons are attributed to different processes.…”
Section: Physical Processes and Driving Mechanismsmentioning
confidence: 99%
“…In the western Pacific warm pool, sea surface freshwater forcing, including the heavy rain under ITCZ and high salinity water subduction from subtropics, are the dominant processes for the BL formation (Anderson et al., 1996; Bosc et al., 2009). Positive BLT anomalies along the eastern and northern coast of the Bay of Bengal during a positive Pacific Decadal Oscillation (PDO) are associated with deepening ILD, referring to enhancing shoreward Ekman transport (Pang et al., 2019). As discussed in Section 4, the BL formations in different seasons are attributed to different processes.…”
Section: Physical Processes and Driving Mechanismsmentioning
confidence: 99%
“…Here the ITD is calculated as the depth where seawater temperature decreases by 0.2 • C from the temperature at 10 m below the surface. This definition has been widely used in literature studies (de Boyer Montégut et al, 2004;Breugem et al, 2008;Pang et al, 2019). The HCT is defined over the upper 400 m as 0 −400 cρTdz, where T is temperature, c is specific heat capacity, and ρ is density.…”
Section: Eddy-induced Anomaliesmentioning
confidence: 99%
“…The development of barrier layers involves various physical mechanisms that regulate the ILD and MLD, including wind‐driven downwelling (e.g., Pang et al., 2019), horizontal advection of low salinity waters (e.g., George et al., 2019), net freshwater fluxes (e.g., Katsura et al., 2022), and relative vorticity (e.g., d’Ovidio et al., 2013). It is suggested that barrier layer thickness (BLT) extends from several meters to a hundred meters and varies temporally and spatially (de Boyer Montégut et al., 2007; Mignot et al., 2007).…”
Section: Introductionmentioning
confidence: 99%